PSVIII-19 Meta-analysis of genetic parameter estimates for feed efficiency traits in dairy cattle - Oliveira, Hinayah (J Anim Sci, 2019)
Over 60% of the production costs in dairy cattle are related to feeding. Genetic selection for improved feed efficiency (FE) is a very promising alternative to reduce feeding costs, increase the industry profitability, and reduce the industry environmental footprints. The success of genetic selection relies in part on the heritability (h(2)) of the indicator traits included in the breeding programs. Several studies have reported h(2) estimates for different FE indicator traits, with a broad range of estimates. To obtain more consistent h(2) estimates across studies and populations, we performed a meta-analysis of published h(2) estimates using four different groups of FE indicator traits commonly used in dairy cattle: 1) energy intake (EI); 2) residual feed intake (RFI); 3) feed (dry-matter) intake (FI); and 4) feed conversion efficiency (FCE). A comprehensive literature review identified 148 h(2) estimates across 39 scientific papers from 13 different countries, published between 1991 and 2019. Thereafter, a meta-analysis based on random-effects model was used to summarize and address the variability of the parameter estimates. Our study confirmed that FE indicator traits in dairy cattle are under moderate genetic control. The h(2) estimates were 0.18±0.02, 0.19±0.02, 0.29±0.01, and 0.19±0.03 for EI, RFI, FI, and FCE, respectively. In addition, our findings showed that h(2) estimates for FE indicator traits in different studies have significant heterogeneity (I(2) index estimated for EI, RFI, FI and FCE was 80.5%, 59.8%, 81.7%, and 55.7%, respectively). Among the possible sources of variation that contributed to the heterogeneity across studies are country, type of housing, life stage, and diet. The results reported here summarize the overall level of genetic control of FE in dairy cattle, which are useful for genetic evaluations when reliable h(2) estimates for FE are not available in the studied dairy cattle population.